Lifetime and recent alcohol use and bone mineral density in adults with HIV infection and substance dependence. Issue 17 (April 2017) - Ventura, Alicia S.; Winter, Michael R.; Heeren, Timothy C.; Sullivan, Meg M.; Walley, Alexander Y.; Holick, Michael F.; Patts, Gregory J.; Meli, Seville M.; Samet, Jeffrey H.; Saitz, Richard
Abstract : Abstract: Low bone mineral density (BMD) is common in people living with HIV infection (PLWH), increasing fracture risk. Alcohol use is also common in PLWH and is a modifiable risk factor for both HIV disease progression and low BMD. In PLWH, alcohol's effect on BMD is not well understood. We studied adult PLWH with substance dependence. We measured lifetime alcohol use (kg) and recent (i.e., past 30-day) alcohol use (categorized as: abstinent, low risk, or high risk). In adjusted multivariable regression analyses, we tested associations between lifetime and recent alcohol use and (i) mean BMD (g/cm 2 ) at the femoral neck, total hip, and lumbar spine and (ii) low BMD diagnosis (i.e., osteopenia or osteoporosis). We also examined associations between 2 measures of past alcohol use (i.e., total consumption [kg] and drinking intensity [kg/year]) and BMD outcome measures during 3 periods of the HIV care continuum: (i) period before first positive HIV test, (ii) period from first positive HIV test to antiretroviral therapy (ART) initiation, and (iii) period following ART initiation. We found no significant associations between lifetime alcohol use and mean femoral neck (β −0.000, P  = .62), total hip (β −0.000, P =  .83) or lumbar spine (β 0.001, P =  .65) BMD (g/cm 2 ), or low BMD diagnosis (adjusted odds ratio [aOR] = 0.98, 95% Confidence Interval [CI]: 0.95–1.01). There was no significant correlation between past 30-day alcohol use and mean BMD (g/cm 2 ). Past 30-day alcohol use was associated with low BMD diagnosis ( P =  .04); compared to abstainers, the aOR for high risk alcohol use was 1.94 (95% CI: 0.91–4.12), the aOR for low risk alcohol use was 4.32 (95% CI: 1.30–14.33). Drinking intensity (kg/year) between first positive HIV test and ART initiation was associated with lower mean BMD (g/cm 2 ) at the femoral neck (β −0.006, P =  .04) and total hip (β −0.007, P =  .02) and increased odds of low BMD (aOR = 1.18, 95% CI = 1.03–1.36). In this sample of PLWH, we detected no association between lifetime alcohol use and BMD. However, recent drinking was associated with low BMD diagnosis, as was drinking intensity between first positive HIV test and ART initiation. Longitudinal studies should confirm these associations. Abstract : Supplemental Digital Content is available in the text